Bimbingan Belajar Pengenalan Huruf Hijaiyah Dengan Metode Talaqqi Kepada Anak di Bawah Umur 10 Tahun Di Desa Pulau Nelayan Sebrang - Zulfirman, Rony; Kustanti, Martin; Amelia, Rezki; Gusmirawati (STAI Tebing Tinggi Deli, 2024)
This research explores how well children in Pulau Nelayan Sebrang Village learnt the Hijaiyah letters using the Talaqqi method. The Talaqqi approach, which prioritises face-to-face communication between educators and learners, was chosen because it has the ability to increase student enthusiasm and engagement - particularly in remote areas where educational opportunities are scarce. Although this method has been widely used in the Islamic educational tradition, there is little data regarding its efficacy in contemporary settings. Using a case study design and qualitative methodology, the research included three months of in-depth interviews and direct observation of parents, teachers and students. The results showed that students' enthusiasm for learning increased and that the Talaqqi approach significantly improved their ability to recognise Hijaiyah letters. In conclusion, although teacher preparation and resource assistance are needed for sustainability, the Talaqqi technique can be a useful substitute for improving basic literacy in places with limited resources.